2019
DOI: 10.1111/ajt.14994
|View full text |Cite
|
Sign up to set email alerts
|

Limited health literacy and adverse outcomes among kidney transplant candidates

Abstract: More than one-third of US adults have limited health literacy, putting them at risk of adverse clinical outcomes. We evaluated the prevalence of limited health literacy among 1578 adult kidney transplant (KT) candidates (May 2014-November 2017) and examined its association with listing for transplant and waitlist mortality in this pilot study. Limited health literacy was assessed at KT evaluation by using a standard cutoff score ≤5 on the Brief Health Literacy Screen (score range 0-12, lower scores indicate wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
62
3
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 54 publications
(75 citation statements)
references
References 47 publications
1
62
3
9
Order By: Relevance
“…We also found study participants with lower health literacy and lower education were more likely to report they felt less knowledgeable about LDKT. Previous studies have demonstrated decreased likelihood of referral for transplant evaluation and lower odds of wait listing among patients with limited health literacy. Poor health literacy may also limit patients' understanding and knowledge of LDKT.…”
Section: Discussionmentioning
confidence: 99%
“…We also found study participants with lower health literacy and lower education were more likely to report they felt less knowledgeable about LDKT. Previous studies have demonstrated decreased likelihood of referral for transplant evaluation and lower odds of wait listing among patients with limited health literacy. Poor health literacy may also limit patients' understanding and knowledge of LDKT.…”
Section: Discussionmentioning
confidence: 99%
“…37 Although we did not measure health literacy directly, education level has been shown to correlate with health literacy in the transplant population. 38,39 Navigating the transplant process, from referral through surgery, has been shown to depend heavily on education, and this need is especially true for living-donor transplantation. 40,41 Fortunately, evidence exists from clinical trials of adult kidney transplant candidates that educational programs can lead to higher knowledge and fewer concerns with living donation as well as an increase in the number of donor inquiries.…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that several reasons could have contributed to our finding of lower likelihood of KT wait‐listing with cognitive impairment. Although we did not aim to use the MoCA score as a proxy for health literacy, patients with MCI have been shown to have lower health numeracy as well as health literacy . Furthermore, many studies have demonstrated a high prevalence of impaired executive function in patients with ESRD .…”
Section: Discussionmentioning
confidence: 99%